The Influence of Consumer Involvement Dimensions on Consumers’ Purchase Intention of Reavers ID Sportswear - Amanda Hajidah Felisha; Yuniarti Fihartini (International Forum of Researchers and Lecturers, 2026)
This study examines the effect of consumer involvement on purchase intention toward Reavers ID sportswear products, focusing on cognitive involvement, affective involvement, enduring involvement, and situational involvement. The research addresses the problem of how different dimensions of consumer involvement influence consumers’ intention to purchase in the context of bazar-based marketing, where purchasing decisions are shaped by both rational evaluation and situational factors. The main objective of this study is to analyze the individual and simultaneous effects of the four involvement dimensions on consumers’ purchase intention. A quantitative approach with a causal design was applied, using survey data collected from 160 respondents who had visited the Reavers ID bazar and showed interest in purchasing sportswear products. Data were analyzed using multiple linear regression with the assistance of SPSS, supported by validity, reliability, and classical assumption tests. The results show that cognitive involvement, affective involvement, enduring involvement, and situational involvement all have positive and significant effects on purchase intention, both partially and simultaneously. Cognitive involvement was found to have the most dominant influence, indicating that rational evaluation of product quality and benefits plays a crucial role in shaping consumers’ buying intentions. These findings suggest that purchase intention is strengthened through a combination of rational consideration, emotional attachment, long-term interest, and supportive purchasing situations. In conclusion, enhancing both informational and experiential aspects of marketing strategies is essential for increasing consumers’ purchase intention toward Reavers ID sportswear products.